Monologue intérieur et discours rapporté : une union problématique ? - Florence FLOQUET (E-REA)
This article aims at studying the link between the literary phenomenon called “interior monologue” and the linguistic techniques of reported speech. While interior monologue is generally described as an autonomous discourse incompatible with narration, I want to show that far from being an oxymoron a reported interior monologue is possible and is in fact the most frequent form for this narratological category. I thus wish to analyse how the various techniques of reported speech represent interior discourse, focusing on the more or less tight link they give the impression to have with the “original” interior discourse: some techniques appear to be at the core of interior monologue (direct speech and “locutionary” free indirect speech), while others dwell at the frontier (“pragmatic” free indirect speech and indirect speech).